Reducing bias in microbiome research: Comparing methods from sample collection to sequencing - Kool, Jolanda; Tymchenko, Liza; Shetty, Sudarshan A.; Fuentes, Susana (Frontiers in Microbiology, 2023)
Abstract BACKGROUND: Microbiota profiles are strongly influenced by many technical aspects which impact the ability of researchers to compare results. To investigate and identify potential biases introduced by technical variations, we compared several approaches throughout the entire workflow of a microbiome study, from sample collection to sequencing, using commercially available mock communities (from bacterial strains as well as from DNA) and multiple human faecal samples, including a large set of positive controls created as a random mix of several participant samples. METHODS: Human faecal material was sampled and aliquots were used to test two commercially available stabilization solutions (Omnigene gut and Zymo Research) in comparison to samples frozen immediately upon collection. In addition, methodology for DNA extraction, input of DNA or number of PCR cycles were analyzed. Furthermore, to investigate the potential batch effects in DNA extraction, sequencing and barcoding, we included 139 positive controls. RESULTS: Samples preserved in both the stabilization buffers limited overgrowth of Enterobacteriaceae when compared to unpreserved samples stored at room temperature (RT). These stabilized samples stored at RT were different from immediately frozen samples, where relative abundance of Bacteroidota was higher and Actinobacteriota and Firmicutes were lower. As reported previously, method used for cell disruption was a major contributor to variation in microbiota composition. Additionally, high number of cycles during PCR lead to an increase in contaminants detected in the negative controls. The DNA extraction had a significant impact on the microbial composition, also observed with the use of different Illumina barcodes during library preparation and sequencing, while no batch effect was observed in replicate runs. CONCLUSIONS: Our study reaffirms the importance of mechanical cell disruption method and immediate frozen storage as critical aspects in faecal microbiota studies. Comparison of storage conditions revealed that the bias was limited in RT samples preserved in stabilization systems, and these may be a suitable compromise when logistics are challenging due to size or location of a study. Moreover, to reduce the effect of contaminants in faecal microbiota profiling studies we suggest the use of ~125 pg input DNA and 25 PCR cycles as optimal parameters during library preparation.